The vagaries of IgM: a case report of EBV infection with concomitantly false-positive IgM for CMV, VZV, and HSV - Raai Mahmood; Khalid Mohamed; Naba Saeed; Kadhim Al-Banaa; Jonathan Zimmerman; Cecilia Big (SpringerOpen, 2020)
Abstract Background Serum IgM (immunoglobulin M) testing is commonly used to diagnose acute viral infections. However, most clinicians are unaware of the vagaries of IgM testing, including antigenic cross-reactivity between multiple viruses and risk misdiagnosis. Case presentation We report a case of infectious mononucleosis with concomitantly positive IgM for EBV, CMV, VZV, and HSV. A 26-year-old man presented with acute infectious mononucleosis picture. His blood work showed a total bilirubin level of 7.7 mg/dl, ALT 1077 U/L, AST 806 U/L, ALP 325 U/L, and INR 1.0. Monospot was positive; peripheral blood smear showed atypical lymphocytes; however, because EBV infectious mononucleosis does not typically cause elevation of liver enzymes over 1000, other etiologies were explored. Tests for hepatitis A, B, C, HIV, ANA, and ASMA returned negative. IgM for EBV-VCA, CMV, HSV, and VZV all returned positive, and the diagnosis of EBV IM was called into question. Subsequent tests of CMV and HSV PCR for viral load were negative (VZV was not clinically suspected), and later on, EBV-EBNA returned negative and EBV-VCA IgM and IgG returned positive, confirming the diagnosis of acute EBV infection. Conclusion We believe that IgM seropositivity can result from cross-reactivity among several viruses (especially herpes viruses), and although often relied on, a positive IgM should not serve as the sole determinant for diagnosis of acute viral infections.